Evaluation of the impact of storage systems on grid electricity demand in the German context - Dennis Metz (2015)
This paper analyzes the impact of storageinstallations on grid electricity demand. Storage systems allowthe decoupling of consumption from electricity generation andtherefore have the potential to change the daily demand profileseen by the network in a significant way. This has far reachingconsequences for many stakeholders, as changes in the netdemand would for example impact electricity prices or changethe requirements for peak generation. The developed approachconsiders the installation of storage devices to increase self consumption of locally generated electricity in a residential andsmall commercial end users context as well as its application forelectricity arbitrage. Assumptions about their implementationon a system level are described and their impact on overallelectricity demand is determined considering the German case.